Environmental protection from emissions of colored waste water by natural sorbent made from cellulose fibers - Djordjevic, Dragan; Urosevic, Snezana; Djordjevic, Suzana (Zaštita materijala, 2017)
Environment protecting from emissions of colored waste water of the textile industry is the subject of this paper. It's about the decolorization with the help of sorbent obtained from natural cellulose fiber waste cotton and hemp. Removal of reactive dye from an aqueous solution by the sorbent was examined under different conditions. It was found that adsorption depends on the contact time, initial dye concentrations and pH of the solution. The used sorbent is a relatively fine dispersion material with heterogeneous porous particles, the diverse shapes and forms, dimensions below 0.7 mm. According to the results of the quantitative composition of the sorbent it is concluded that dominates the carbon, carbon content 67.26 %. The maximum degree of dye removal occurs at pH 2-3 (68.5 %). The adsorbed amount of dye on the sorbent over time increases with increasing initial concentration. Isothermal models, Langmuir and Freundlich, very well describe the removal of reactive dye from aqueous solution with the help of sorbent (coefficients of determination = or > 0.9), with the notion that advantage is given to the nonlinear Freundlich model that best describes experimental data.